CERTAIN TRANSFORMATIONS OF BASIC AND POLY-BASIC HYPERGEOMETRIC SERIES - Ali, S. Ahmad; Rizvi, S. Nadeem Hasan (Italian Journal of Pure and Applied Mathematics, 2015)
In the present work, certain new transformations of basic and poly-basic hypergeometric series have been established with the help of Bailey lemma.